2009
DOI: 10.1099/ijs.0.65742-0
|View full text |Cite
|
Sign up to set email alerts
|

Re-examination of the taxonomic position of Bacillus silvestris Rheims et al. 1999 and proposal to transfer it to Solibacillus gen. nov. as Solibacillus silvestris comb. nov.

Abstract: Re-examination of the taxonomic position of Bacillus silvestris Rheims et al. 1999 Following the transfer of three of the six species enclosed in the original definition of rRNA group 2 of Bacillus to the genus Sporosarcina and two to Lysinibacillus, other species of this group, some of which were added later, still await taxonomic revision. In a recent publication, a set of 'core' characteristics was proposed for species to be included in the genus Bacillus (Kä mpfer et al., 2006). Except for Bacillus silves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…Interestingly, the lipid profiles of the two strains overlapped completely, with no spots appearing in one but not the other. These profiles once again match well with the original species description of S. silvestris (Krishnamurthi et al, 2009a). However, there were discrepancies with the lipid data reported by Shivaji et al (2009); they did not find diphosphatidylglycerol in B. isronensis.…”
Section: B Isronensis B3w22supporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, the lipid profiles of the two strains overlapped completely, with no spots appearing in one but not the other. These profiles once again match well with the original species description of S. silvestris (Krishnamurthi et al, 2009a). However, there were discrepancies with the lipid data reported by Shivaji et al (2009); they did not find diphosphatidylglycerol in B. isronensis.…”
Section: B Isronensis B3w22supporting
confidence: 82%
“…The accession numbers for the ITS region sequences of B. subtilis MTCC 121 the reclassification of B. fusiformis and B. sphaericus to the genus Lysinibacillus and B. insolitus to the genus Psychrobacillus, respectively. It has been recognized that species classified as members of the genus Bacillus within this group should be placed either in a new genus or into already existing genera; examples include the proposal of the genera Viridibacillus (Albert et al, 2007) and Solibacillus (Krishnamurthi et al, 2009a). However, microbiologists have continued to describe novel taxa within this group as members of Bacillus, e.g.…”
Section: An Investigation Into the Taxonomic Position Of Bacillus Isrmentioning
confidence: 99%
“…Gram-negative and Gram-positive bacteria contain 713/1542 and 568/1542 nucleotides, respectively, in the highly conserved regions [30], and a total of 145/1542 (9.4%) more nucleotides are conserved in Gram-negative bacteria. Under these circumstances, the difference of 88 to 93% among species of Clade1, Clade2 and Clade3, being Gramnegative by virtue, belonging to the genus Hymenobacter, is huge and demands the creation of new genera [30], since earlier the genera were carved with >92% 16S rRNA gene sequence similarity [7,8,[32][33][34]. The main impediment is the lack of diagnostic phenotypic differences.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, it is worth mentioning that, based on 16S rRNA gene sequence analyses, five distinct phylogenetic groups within the genus Bacillus [3], two novel orders, Solirubrobacterales and Thermoleophilales [4], and a new hierarchic classification structure for the actinomycete line of descent [5] were proposed and the phylogenetic affiliation of the genus pseudomonads was assessed [6]. In congruence with these, to take few examples, several novel genera, such as Solibacillus [7] and Planomicrobium [8], were created on the basis of their 16S rRNA gene sequence. Present work is focused on evaluating the internal features of the 16S rRNA gene sequences of the genus Hymenobacter.…”
Section: Introductionmentioning
confidence: 99%
“…Suihko and Stackebrandt [29], Suominen et al [30] and Väisänen et al [31] all found Bacillus and Paenibacillus in final recycled food packaging paper and board. Suihkoand Stackebrandt [29] also found Bacillus silvestris, which has since been renamed Solibacillus silvestris [32], a genus present in our study. Likewise, McCusky Gendron et al [11] and Namjoshi et al [33] found Bacillus and Paenibacillus on unused paper towels and linerboard, respectively.…”
Section: Comparison Of the Bacterial Communities Obtained Using 454 Pmentioning
confidence: 87%